Femur fractures in the elderly patient and the public health service in the Amazon region (Research, Society and Development, 2020)
Objective: To carry out an epidemiological investigation, in the period from 2009 to 2018, on femur fracture in the elderly and its implications for the health service in the city of Belém, Pará. Methodology: Quantitative, retrospective and descriptive research, of a historical series in the period from 2009 to 2018, in the city of Belém, Pará, supported by scientific articles in order to expose an overview of hospitalizations of elderly people for femur fractures in the last decade and the public health system. The data were extracted from the Unified Health System and processed in the Bioestat® 5.3 program. Results: Hospitalizations of patients with femoral fractures present a greater tendency in more advanced age groups, as well as a predominance of the number of female patients, over male patients, in elderly patients. In addition, they represent a high cost for public health services. Conclusion: The data obtained by this research are consistent with the expected pattern and reported by the literature.